2020
DOI: 10.1111/1749-4877.12508
|View full text |Cite
|
Sign up to set email alerts
|

A pioneering survey of deep‐diving and off‐shore cetaceans in the northern South China Sea

Abstract: A pioneering boat-based survey was conducted in 2019, to gather baseline information regarding the presence, composition, relative abundance, and spatial distribution of deep-diving and off-shore cetaceans in the northern South China Sea (SCS). A total of 27 sightings comprising at least 8 cetacean species were recorded during the 13-day survey, including 5 deep-diving species (i.e. Risso's dolphin [Grampus griseus], short-finned pilot whale [Globicephala macrorhynchus], sperm whale [Physeter macrocephalus], C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The scientific expedition was conducted onboard the 50‐m‐long RV Tian'e from April 26 to May 10, 2019 (for details, see Lin et al . 2020). The study area extended on the northern part of the South China Sea (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific expedition was conducted onboard the 50‐m‐long RV Tian'e from April 26 to May 10, 2019 (for details, see Lin et al . 2020). The study area extended on the northern part of the South China Sea (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Rosso M, Lin M, Caruso F et al (2021). First live sighting of Deraniyagala's beaked whale (Mesoplodon hotaula) or ginkgo-toothed beaked whale (Mesoplodon ginkgodens) in the western Pacific (South China Sea) with preliminary data on coloration, natural markings and surfacing patterns.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Of the 8 encountered species, 7 were recorded at sea in the northern South China Sea for the first time. Through using photographic data, Rosso et al (2021) identified a group of mysterious beaked whales from the field survey depicted by Lin et al (2021a). Photographic evidences showed that the mysterious beaked whales are either ginkgo-toothed or Deraniyagala's beaked whales (Mesoplodon ginkgodens or M. hotaula).…”
Section: Multiple-species Field Surveysmentioning
confidence: 99%
“…In this volume, Lin et al . (2021a) presented a first attempt to investigate deep‐diving and off‐shore cetaceans in the northern waters of South China Sea. This study presented a high diversity of cetacean species in the survey area.…”
Section: Ecology and Behaviormentioning
confidence: 99%
See 1 more Smart Citation